The Ethnographer’s Apprentice: Trying Consumer Culture from the Outside In - Sherry, John F. (Journal of business ethics, 2008)
Anthropologists have long wrestled with their impact upon the people they study. Historically, the discipline has served and subverted colonial agendas, but views itself traditionally as an advocate for the disempowered and as an instrument of public policy. Marketing is now among the pre-eminent institutions of cultural stability and change at work on the planet. Currently, ethnography is assuming a growing importance in the marketer’s effort to influence the accommodation and resistance of consumers to the neocolonial forces of globalization. The ethical consequences of market-oriented ethnography are explored in this essay.